Application of the protein semisynthesis strategy to the generation of modified chromatin - Holt, Matthew; Muir, Tom (Annual review of biochemistry, 2015)
Histone proteins are subject to a host of posttranslational modifications (PTMs) that modulate chromatin structure and function. Such control is achieved by the direct alteration of the intrinsic physical properties of the chromatin fiber or by regulating the recruitment and activity of a host of trans-acting nuclear factors. The sheer number of histone PTMs presents a formidable barrier to understanding the molecular mechanisms at the heart of epigenetic regulation of eukaryotic genomes. One aspect of this multifarious problem, namely how to access homogeneously modified chromatin for biochemical studies, is well suited to the sensibilities of the organic chemist. Indeed, recent years have witnessed a critical role for synthetic protein chemistry methods in generating the raw materials needed for studying how histone PTMs regulate chromatin biochemistry. This review focuses on what is arguably the most powerful, and widely employed, of these chemical strategies, namely histone semisynthesis via the chemical ligation of peptide fragments.